Bariery społeczne występujące między pracownikami PGR a rolnikami indywidualnymi - Stukin, Kazimierz (Wydział Prawa i Administracji UAM, 1983)
The task of this article is to find whether and to what extent, there are social barriers observed between individual farmers and workers of State farms interfering in the process of intercommunication of both communities. The social barrier is understood here as a subjective or objective state hindering the co- -existence of a given category of people or groups. This barrier can be therefore understood both as a psychological phenomienon (autodefinition and definition of the interaction partners) and a sociological one (type of behavior, type of relations between definite social categories). Consequently, the confrontation in three aspects was aimed art,, i.e.: ,1) functioning of mutual opinions, 2) social contacts occurring actually, 3) objective similarities and différences. The initial data for analysis contained results of empirical research carried out among indvidual farmers (village), workers of a State farm localized in the village and workers of a State farm localized outside of the village. In the last instance, space was the main determinaint of the existing social relations and, at the same time, a reference to the situation where it was of a secondary importance. The following was found at the outcome of the investigation: 1) one cannot say that economic and educational barriers are present in the examined categories, 2) spatial isolation of a State farm outside of the village can limit, to a large extent, the intergroup communie ability, deforming thus opinions on individual farmers in categories of overestimation,, 3) the demographic barrier can be observed, especially in is element of age, 4) the psychological barrier is also present, it is rooted in stereotypes.
Social barriers observed between workers of State farms and individual farmers